2014
DOI: 10.1248/bpb.b14-00278
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Administration of Aqueous Pregabalin Solution as a Potential Treatment Option for Patients with Neuropathic Pain to Avoid Central Nervous System-Mediated Side Effects

Abstract: Pregabalin, (S)-3-isobutyl-γ-aminobutyric acid (GABA), is a widely used adjuvant therapy for patients with neuropathic pain, which is defined as chronic pain caused by lesions or diseases of the somatosensory nervous system. However, dizziness and somnolence (sleepiness) are common dose-limiting side effects, probably due to excessive sedative effects on higher centers of the central nervous system (CNS) which are involved in the anticonvulsant and analgesic actions of pregabalin. We speculated that transderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…In the present work; inclusion of PG in niosomal hydrogel preparation is of great importance as many reported PG formulations including PG conventional topical gel 15 , PG patch 16 and PG solution 17 were not enhanced with such innovative nano-vesicles, resulting in the lacking of their ability to deliver PG in controlled pattern with good skin permeation profiles to achieve the bioavailability augmentation.…”
mentioning
confidence: 99%
“…In the present work; inclusion of PG in niosomal hydrogel preparation is of great importance as many reported PG formulations including PG conventional topical gel 15 , PG patch 16 and PG solution 17 were not enhanced with such innovative nano-vesicles, resulting in the lacking of their ability to deliver PG in controlled pattern with good skin permeation profiles to achieve the bioavailability augmentation.…”
mentioning
confidence: 99%
“…Some studies have also reported the analgesic effect of transdermal pregabalin preparations, that is, an aqueous solution or PLO gel of pregabalin 9,21 . According to one report, 9 an aqueous solution of pregabalin (0.25 or 0.75%) had a significant analgesic effect 1.5 h after application in a spinal nerve ligation model in mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has side effects, such as dizziness, somnolence (sleepiness), and edema, which may be severe enough to be either dose‐limiting or lead to discontinuation in clinical practice 8 . In a previous study, transdermal application of an aqueous pregabalin solution was reported to be effective against neuropathic pain in rats and mice 9 . Since the central nervous system (CNS)‐mediated side effects of orally administered pregabalin are expected to be avoided or minimized by transdermal delivery of the drug, topical application via the transdermal route would substantially benefit patients.…”
Section: Introductionmentioning
confidence: 99%
“…Its primary effect is anticonvulsant, and it is used in epilepsy. 9,10 Its mechanism of action is still not fully resolved, although it has been found to bind to the calcium channel in the central nervous system and reduce calcium flow at the nerve endings. Thus, it is thought to change the release of neurotransmitters that reduce the communication between nerves and be effective in neuropathic pain and epilepsy seizures.…”
Section: Introductionmentioning
confidence: 99%